Cost optimization of bathroom scale by using Boothriyd-Dewhurst DFA method - Nornadia, Annuar (2010)
The ability to quickly develop new products,which are of the lowest cost, the highest quality and the fewest environment impact, as a key factor to meet a global market demand. Design for manufacture and assembly (DFMA) has been most widely applied in industries with most impressive achivements. There are three well-known DFMA tools: Boothryod-Dewhurst only. This project is about analyzing the cost optimization of bathroom scale by using DFMA method. The method will help to identify the unnecessary component inside the bathroom scale and help to minimize the assembly time hence reduce the cost of the product. After evaluate the current design the design efficiency is 28.86% and the assembly cost is RM 0.30418. By using boothroyd-Dewhurst method, created five new designs for bathrooms scale and make analysis for each design using Boothroyd-Dewhurst manual handling and insertiontable. From the esult, design five has the highest design efficiency which is 36.11% and the assembly cost is the lowest from other design which is RM 0.22659. When implementing the new design in the bathroom scale production line, the productivitiy of the product increases from 16 productspe hour to 20 products per hour. The totalassembly times reduce from 3.6387 minutes to 2.9082 minutes. And the labour rate decreases from RM 0.3125 to RM 0.25. Current design has total parts of 25 mean while new design only have 23 parts.